Study the Efficacy of Tranexamic Acid in Reducing Blood Loss During L.S.C.S. - Bhatia, Dr. Baljeet Kaur; Vachhani, Dr. Rashim; Ratnani, Dr. Rekha (International Journal of Innovative Research in Medical Science, 2018)
This is a randomized controlled study for the effectiveness of tranexamic acid to reduce blood loss during caesarean section. The study was undertaken at the department of obstetrics and gynaecology At CCM Medical College. The patients who were not given tranexamic acid during caesarean section were taken in control group and those who received tranexamic acid were taken in study group. Standardisation was done for administration of drug and patient monitoring, and amount of blood loss and possible side effects of drug on mother and neonate were recorded.